Contribución de Pseudomonas putida en la adaptación de Arabidopsis thaliana al estrés alcalino - López Hernández, José (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Soil alkalinity is one of the main factors affecting plant growth, as it interferes with root development and affects their ability to acquire nutrients and water. Although significant advances have been made in recent years in understanding the relationships of calcareous soils with the availability of nutrients such as phosphorus, nitrogen, and iron, to date, a detailed study of how plants grow and adapt to moderate and high alkalinity conditions has not been conducted. In this work, the effects of alkalinity on the growth and development of Arabidopsis thaliana in vitro were investigated. To do this, we analyzed the growth of normal plants of the Columbia-0 (Col-0) ecotype by increasing the pH of the growth medium from 7.0 to 9.0. Our results show that A. thaliana is unable to grow properly as the pH of the substrate increases, as the mitotic activity of foliage and root meristems is disrupted, which blocks organogenesis. Consequently, photosynthesis and overall plant development are compromised. The analysis was complemented by a study of the expression of localization reporter genes in meristems (CYCB1:GUS, TOR:GUS) and inducible by auxins (DR5:GUS) and cytokinins (ARR5:GUS) to determine the physiological state of the plants. The increase in pH decreased the expression of the four reporter genes analyzed, suggesting that the drastic repression of growth by alkalinity implied a reduction in meristematic activity, as well as hormonal imbalances critical for plant survival. The microbiome helps plants survive various types of stress. The interactions of bacteria with plants expand the functions performed by each organism, creating great expectations for agricultural improvement through the engineering of the rhizosphere. This is achieved through the inoculation of selected bacterial strains, which, due to their properties such as nutrition, hormonal balance, and growth modulation, can enhance plant growth. We selected Pseudomonas putida as a promising bacterium to help plants resist alkaline stress, due to its properties, including the production of cyclodipeptides with auxin activity, which promote root development.

La alcalinidad del suelo es uno de los principales factores que afectan el crecimiento de las plantas, ya que interfiere con el desarrollo de las raíces y afecta su capacidad para adquirir nutrientes y agua. Aunque se han logrado avances significativos en los últimos años en la comprensión de las relaciones de los suelos calcáreos con la disponibilidad de nutrientes como el fósforo, el nitrógeno y el hierro, hasta la fecha no se ha realizado un estudio detallado de cómo las plantas crecen y se adaptan a condiciones de alcalinidad moderada y alta. En este trabajo, se investigaron los efectos de la alcalinidad sobre el crecimiento y desarrollo de Arabidopsis thaliana in vitro. Para ello, analizamos el crecimiento de plantas normales del ecotipo Columbia-0 (Col-0) incrementando el pH del medio de crecimiento desde 7.0 a 9.0. Nuestros resultados muestran que el desarrollo de A. thaliana se ve afectado conforme aumenta el pH del medio, ya que la actividad mitótica de los meristemos del follaje y de la raíz se interrumpe, lo que bloquea la organogénesis y con ello la fotosíntesis y el desarrollo general de las plantas. El análisis se complementó con un estudio de la expresión de genes reporteros de localización en los meristemos (CYCB1:GUS, TOR:GUS), e inducibles por auxinas (DR5:GUS) y citocininas (ARR5:GUS) para conocer el estado fisiológico de las plantas. El incremento en el pH disminuyó la expresión de los genes reporteros analizados, sugiriendo que la drástica represión del crecimiento por efecto de la alcalinidad implica una reducción de la actividad meristemática, así como desequilibrios hormonales críticos para la sobrevivencia de las plantas. Seleccionamos a Pseudomonas putida como una bacteria prometedora para ayudar a las plantas a resistir el estrés alcalino, por algunas de sus propiedades como la producción de ciclodipéptidos con actividad auxínica, que promueven el desarrollo de la raíz.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2025-0937; Rizobacteria; Alcalinidad; Estrés abiótico en plantas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19381